Strategi Influencer Marketing dan Tantangan Vampire Effect dalam Pembentukan Identitas Merek di Kalangan Gen Z - Chrisania, Liaga; Teofilus, Teofilus (Syntax Literate, 2025)
This study aims to analyze the effect of influencer credibility on influencer popularity, as well as to examine the role of the vampire effect as a moderating variable in the context of digital marketing strategies targeting Gen Z. The background of this research is driven by the growing use of influencers in digital marketing strategies, while challenges remain when the influencer’s persona becomes more dominant than the brand message delivered. A quantitative approach was employed, using a survey method targeting Gen Z respondents in Indonesia. Data were analyzed using linear regression and moderation testing. The results indicate that influencer credibility has a positive but insignificant effect on influencer popularity. Meanwhile, the vampire effect has a direct influence on influencer popularity but does not significantly moderate the relationship between influencer credibility and popularity. The managerial implication of this study suggests that companies should carefully consider influencer credibility while anticipating the potential impact of the vampire effect when selecting influencers as part of digital marketing strategies. Furthermore, this research opens opportunities for future studies using a mixed-method approach, as well as exploring other variables such as audience involvement and emotional engagement.